Temporal Leadership and Bootlegging Behavior of Employees: The Mediating Effect of Self-Efficacy - Li, Mingze; Ye, Huili (Frontiers in Psychology, 2021)
As an important source of innovation, bootlegging is widespread in organizations. However, a lack of understanding exists of its antecedents. Based on the social cognition theory, this study explores when and how temporal leadership leads to employee's bootlegging behaviors. By collecting two-stage questionnaire data from 231 employees, we drew the following conclusions: temporal leadership can promote employee's bootlegging behavior; self-efficacy had a mediating effect between temporal leadership and bootlegging; perceived team-efficacy had a moderating effect between temporal leadership and self-efficacy; and perceived team-efficacy moderated the indirect effect of temporal leadership on bootlegging through self-efficacy. Specifically, when perceived team-efficacy was lower, the indirect effect was stronger. This study revealed the internal mechanism between time management and bootlegging, which provided an instructive view for further study on organizational innovation management.